Development of Rare Plant Nurseries in Support of Conservation of the UNNES Campus Surrounding Area - Martuti, Nana Kariada Tri; Herlina, Lina; Aji, Ananto; Nazar, Lutfian (Universitas Negeri Semarang, 2025)
As a conservation-oriented university, UNNES has carried out various activities that support the preservation of nature and the environment. The increasing development of UNNES has led to an increasing diversity of community activities around it, thus potentially creating environmental impacts due to the increasingly massive land conversion for business, housing and entertainment. This condition indirectly affects the existence of flora and fauna in the UNNES Campus environment. To anticipate this condition, UNNES has undertaken various environmental improvement efforts, one of which is by regularly carrying out planting programs. It is fitting that UNNES has its own nursery in collaboration with the fostered community partners. The Akar Banir Foundation as a partner in community service activities, is a foundation that already has good capabilities in cultivating various types of plants. The objectives of this community service activity are: a) to facilitate a shaded house for a representative rare plant nursery and b) to develop and increase the biodiversity of rare plant seeds that will be developed by Akar Banir. From this community service activity, the following results have been achieved: a shaded house for a rare plant nursery located at Ecofarm UNNES Semarang with an area of 3 x 12 m2 . This shade house provides a facility for developing rare plant seedlings, which is expected to contribute to preserving Indonesia's rare plant germplasm. To date, 21 rare Indonesian plant species have been developed, and the hope is that this will continue to grow.